Genome analysis of SARS-CoV-2 isolates occurring in India: Present scenario - Ragunathan Devendran; Manish Kumar; Supriya Chakraborty (Wolters Kluwer Medknow Publications, 2020)
Background: The origin of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is still a debatable topic. The association of the virus spread from the market is supported by the close relation of genome sequences of environmental surface samples with virus samples from earliest patients by phylogenetic analysis. Objectives: To have an insight into the SARS-CoV-2 genome sequences reported from India for better understanding on their epidemiology and virulence. Methods: Genome sequences of Indian isolates of SARS-CoV-2 were analyzed to understand their phylogeny and divergence with respect to other isolates reported from other countries. Amino acid sequences of individual open reading frames (ORFs) from SARS-CoV-2 Indian isolates were aligned with sequences of isolates reported from other countries to identify the mutations occurred in Indian isolates. Results: Our analysis suggests that Indian SARS-CoV-2 isolates are closely related to isolates reported from other parts of the world. Most ORFs are highly conserved; mutations were also detected in some ORFs. We found that most isolates reported from India have key mutations at 614th position of the S protein and 84th position of the ORF 8, which has been reported to be associated with high virulence and high transmission rate. Conclusion: An attempt was made to understand the SARS-CoV-2 virus reported from India. SARS-CoV-2 reported from India was closely similar to other SARS-CoV-2 reported from other parts of the world, which suggests that vaccines and other therapeutic methods generated from other countries might work well in India. In addition, available sequence data suggest that majority of Indian isolates are capable of high transmission and virulence.